2019
DOI: 10.24869/psyd.2019.141
|View full text |Cite
|
Sign up to set email alerts
|

Is Brain-Derived Neurotrophic Factor (Bdnf) Val66met Polymorphism Associated With Obsessive-Compulsive Disorder? A Meta-Analysis

Abstract: Background: Brain-derived neurotrophic factor (BDNF) polymorphism plays an important role in neural survival and was proposed to be related to obsessive-compulsive disorder (OCD). Genetic association studies of the BDNF Val66Met polymorphism (rs6265) in OCD have produced inconsistent results. A meta-analysis of studies was conducted to compare the frequency of the BDNF Val66Met variant between cases with OCD and age-matched controls.Subjects and methods: Electronic databases were searched for eligible articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The main findings of our studies indicate that the Val66Met polymorphism is not associated with OCD. Two prior meta-analyses have indicated that the Val66Met polymorphism is not related to OCD, which was in agreement with our findings ( 8 , 20 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The main findings of our studies indicate that the Val66Met polymorphism is not associated with OCD. Two prior meta-analyses have indicated that the Val66Met polymorphism is not related to OCD, which was in agreement with our findings ( 8 , 20 ).…”
Section: Discussionsupporting
confidence: 94%
“…While previous evidence suggests that the rs6265 polymorphism is involved in the etiology of OCD, the outcomes of such studies have been inconsistent and even contradictory. Findings from the latest meta-analytic investigation by Wang et al in 2019 provide little support for the Val66Met variant as a predictor of OCD ( 8 ). In order to derive a more putative conclusion, an updated meta-analysis was performed to study the connection between the rs6265 polymorphism of the BDNF gene and the risk of OCD.…”
Section: Introductionmentioning
confidence: 99%
“…Most genetic studies have focused on the role of the brainderived neurotrophic factor (BDNF) in the pathophysiology of mental disorders, including OCD. 4 BDNF is a member of the neurotrophin family and it plays an important role in neuronal survival, differentiation, synaptic efficiency, neuronal plasticity, and neurotransmitter function. 5 The genetic variation of this gene that has been the most widely studied is 196G/A, which produces a functional change in the Val66Met amino-acid (rs6265).…”
Section: Introductionmentioning
confidence: 99%
“…Altered levels of BDNF have also been related to impulsiveness in PTSD [12] and could be therefore considered a link between OCD and PTSD. However, evidence of the role of BDNF in OCD is still weak [13].…”
Section: Introductionmentioning
confidence: 99%